Pharmacognostical and Physico-Chemical Investigations of Albizia lebbeck benth. Flower - Yadav, Shyamlal Singh (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAlbizia lebbeck benth, commonly known as Shirisha in Sanskrit and Hindi is a medium to large tree belonging to the family Fabaceae (formerly Leguminaceae) and a member of subfamily Mimosaceae. Different parts of the plant have been explored for activities like anti-inflammatory, anti-histaminic, anti-anaphylactic, anti-asthmatic, anti-microbial etc. Pharmacognostic features of the plant parts like bark and leaf have found available for reference, but the same is not in case flowers of Albizia lebbeck benth. Considering this, the current study has been planned. The diagnostic characters of flower of this plant are presence of warty trichomes, lignified fibers, tannin containing cells, prismatic crystals and pollen grain. Physicochemical studies revealed loss on drying (8.35 % w/w), total ash (7.30 % w/w), acid insoluble ash (0.889% w/w), alcohol-soluble extractive (43.80% w/v) and water-soluble extractive (31.60% w/v). The information generated in this study will provide a lead towards providing relevant pharmacognostical and physicochemical data, which is needed for proper identification and authentication of flower of this particular species.Key words: Albizia lebbeck benth, Ayurveda, Pharmacognosy, Shirisha.